Path Analysis: Application of Health Belief Model and Social Cognitive Theory in Smoking Cessation in Surakarta - Muhammad Fahrezi Al Ghifari; Argyo Demartoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2024)
Background: Smoking is harmful to health. The percentage of smoking in Surakarta City is 23.11%. This study aims to analyze the theory of social cognitive and health belief models in smoking cessation behavior in Surakarta, Central Java. Subjects and Method: It was a cross-sectional study conducted in Surakarta City from September to November 2023. A total of 200 adults aged ≥15 years were selected using snowballing sampling in the study. The dependent variable was smoking cessation behavior. The independent variables were perceived susceptibility, perceived severity, perceived benefits, perceived barriers, perceived cues to action, self-efficacy, observational learning, reinforcement, expectations, expectancy, and behavioral capabilities. Results: Self-efficacy had a direct effect on smoking cessation behavior (b = 3.30; CI 95%= 2.54 to 4.06; p<0.001). Perceived benefits, perceived barriers, cues to action, perceived severity, perceived susceptibility, and observational learning had indirect effects on smoking cessation behavior. Conclusion: Self-efficacy has a direct effect on smoking cessation behavior. Perceived benefits, perceived barriers, cues to action, perceived severity, perceived susceptibility, and observational learning have indirect effects on smoking cessation behavior.